Impact of RCTs under Rice-Wheat cropping system in Indo- Gangetic Plains of India: A review - Kharia, Sushil Kumar; Goyal, Avinash; Jinger, Dinesh; Yadav, Brijesh (Annals of Agricultural Research, 2018)
The rice and wheat production practices are changing with the influence of several factors like water availability, labour and climate conditions. Conversion from conventional agriculture to conservation agriculture may be efficient solution for maximizing grain production and supply food to growing population.Resource conservation practices (RCTs) such as direct seeding of rice, zero tillage of wheat, rice residue either as mulch or incorporated into the soil significantly improved physical, chemical as well as biological properties of soils. As a result, yield and yield attributing parameters also improved due to better soil conditions created by using RCT’s. For improving the farmers profitability in Indo-Gangetic Plains- a prototype shift is necessary. Based on experiments on different regions certain practice such as resources conserving practices are proposed to increase system productivity. Long term assessment of these practices under different climatic conditions will reflect on efficiency of these practices.In this review, an attempt was made to highlight different issues in rice-wheat system, which must be considered to develop policy for improving the productivity and sustainability of this system.